Pendampingan Peningkatan Pendapatan UMKM yang Terdampak Covid-19 melalui Perbaikan Pengelolaan Manajemen Keuangan dan Digital Marketing: Assistance in Increasing the Income of MSMEs Affected by Covid-19 through Improved Financial Management and Digital Marketing - Supardi, Supardi; Yulianto, Mochamad Rizal; Sumarno, Sumarno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Through better financial management and digital marketing, the study seeks to raise the income of MSMEs impacted by COVID-19. Due to a pandemic of MSME business players, there are a number of issues, including decreasing sales, ineffective advertising, and a lack of business fund management expertise, all of which have a negative impact on MSME entrepreneurs’ revenue. This study is quantitative and relies on respondents’ responses to a questionnaire survey. Multiple linear regression analysis was performed in the data analysis process. The t-test was employed to examine the independent variable’s partial impact on the dependent variable. The f test is utilized to examine the combined impact of the independent and dependent variables on the dependent variable. The outcomes of data processing demonstrate that better financial management and digital marketing have an impact on raising the income of Micro, Small, and Medium Enterprises affected by COVID-19. When viewed collectively, the independent and dependent variables have an impact on one another. by employing sound financial management and digital marketing to boost the revenue of Covid-19-affected Micro, Small, and Medium Enterprises.